Gastric emptying of a solid meal is accelerated by the removal of dietary fibre naturally present in food. Issue 6 (June 1995) - Benini, L; Castellani, G; Brighenti, F; Heaton, K W; Brentegani, M T; Casiraghi, M C; Sembenini, C; Pellegrini, N; Fioretta, A; Minniti, G
Abstract : Exogenous fibre added to liquid meals delays gastric emptying. Its effect on solid meals is uncertain, and nothing is known of the effect on gastric emptying of fibre naturally present in food. This study therefore looked at gastric emptying of two different solid meals in eight healthy subjects and their blood glucose responses. The meals were exactly equivalent except for the total dietary fibre content (high fibre 20 g, low fibre 4 g of dietary fibre per 1000 kcal) and supplied 870 kcal (700 kcal women), 47% of which was from carbohydrates, 36% from fats, and 17% from proteins. Ultrasonography was used to measure antral diameters before the meal (basal), immediately after it (time 0), and at 30, 60, 120, 180, 240, and 300 minutes. In addition, subjects filled in a questionnaire on their feelings of hunger, epigastric fullness, and satiety before the meal and at hourly intervals after it. Basal and maximal postprandial antral sections were similar for the two meals (basal section: 283.9 (29.5) v 340.9 (44.7) mm2 for the low and the high fibre meal, NS; maximal postprandial section: 1726 (101.9) v 1593 (120.4) mm2, NS). Total gastric emptying time was significantly reduced by fibre removal (186.0 (15.6) v 231.7 (17.3) minutes after the low and the high fibre meal, p < 0.05). Blood glucose was higher after the low fibre meal, and the area under the glycaemic curve significantly greater (226 (23.1) v 160 (20.0) mmol/min/dl-1, p < 0.05). No difference was found in satiety or fullness feelings, but hunger returned more rapidly after the low fibre meal. In conclusion, fibre naturally present in food delays gastric emptying of a solid meal, reduces the glycaemic response, and delays the return of hunger.